Several audiotapes containing broadcasts of "Another voice of freedom", "Stimme der Freiheit", propagating anti-semitism and racism
Several audiotapes containing broadcasts of "Another voice of freedom", "Stimme der Freiheit", propagating anti-semitism and racism.